The NRU and the Evolution of Regional Disparities in Spanish Unemployment - Roberto Bande; Marika Karanassou (European Regional Science Association (ERSA), 2012)
On both theoretical and empirical grounds, this paper provides evidence that refutes the natural rate of unemployment (NRU) hypothesis as an explanation of the evolution of regional disparities in the unemployment rate. We first present our analytical framework, which follows the chain reaction theory (CRT) of unemployment and argues that (i) a system of interactive labour market equations, rather than a single-equation unemployment rate model, is better equipped to accommodate unemployment dynamics, and (ii) due to the interplay of frictions and growth in labour markets, the NRU ceases to be an attractor of the unemployment rate time path. We then provide evidence that the Spanish economy is characterised by large and persistent disparities in the regional unemployment rates. Through standard kernel density tecnhiques, we demonstrate the existence of marked differences between two groups of high and low unemployment regions that remain stable in their composition through time. Finally, we review our empirical labour market model for each group of regions and evaluate the corresponding natural rates. Our findings confirm that the evolution of regional disparities cannot be attributed to disparities in the natural rates, given that these, although different, do not act as an attractor of unemployment. Thus, the NRUs offer little help in the formulation of labour market policies.
Keywords: 330